2024
DOI: 10.1002/bdr2.2334
|View full text |Cite
|
Sign up to set email alerts
|

The timing, duration, and severity of nausea and vomiting of pregnancy and adverse birth outcomes among controls without birth defects in the National Birth Defects Prevention Study

Nina L. Schrager,
Samantha E. Parker,
Martha M. Werler

Abstract: BackgroundNausea and vomiting of pregnancy (NVP) occurs in approximately 70% of pregnant people, with varying severity and duration. Treatments include pharmacologic and herbal/natural medications. The associations between NVP and birth outcomes, including preterm birth, small for gestational age (SGA), and low birth weight are inconclusive.ObjectiveTo determine whether NVP and reported medications are associated with adverse birth outcomes.MethodsWe used data from the population‐based, multisite National Birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 61 publications
2
1
0
Order By: Relevance
“…Beyond the severity and symptomology of NVP, there is some evidence that the timing and duration of NVP also matters. In a recent analysis of the US National Birth Defects Prevention Study, NVP in the first trimester was associated with a reduced risk of small-for-gestation-age birth, in line with earlier studies which found a general positive association between NVP and better birth outcomes [ 57 ]. However, in the same study, NVP lasting beyond early pregnancy into the second and third trimester was associated with an increased risk of preterm birth [ 57 ].…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…Beyond the severity and symptomology of NVP, there is some evidence that the timing and duration of NVP also matters. In a recent analysis of the US National Birth Defects Prevention Study, NVP in the first trimester was associated with a reduced risk of small-for-gestation-age birth, in line with earlier studies which found a general positive association between NVP and better birth outcomes [ 57 ]. However, in the same study, NVP lasting beyond early pregnancy into the second and third trimester was associated with an increased risk of preterm birth [ 57 ].…”
Section: Introductionsupporting
confidence: 78%
“…In a recent analysis of the US National Birth Defects Prevention Study, NVP in the first trimester was associated with a reduced risk of small-for-gestation-age birth, in line with earlier studies which found a general positive association between NVP and better birth outcomes [ 57 ]. However, in the same study, NVP lasting beyond early pregnancy into the second and third trimester was associated with an increased risk of preterm birth [ 57 ]. Similarly, in an analysis of the Swedish Medical Birth Register, women who experienced in-patient treatment for HG in the first trimester only had a slight increased risk of pre-eclampsia compared to baseline, while women who experienced in-patient treatment for HG in the second trimester experienced significant increased risks of pre-term pre-eclampsia, placental abruption and small-for-gestational-age birth [ 58 ].…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation